Copper-Catalyzed S-Arylation of Arylthioureas by Using Diaryliodonium Salts - Zhu, Hui; Liu, Xing; Cheng, Yu; Peng, Han-Ying; Li, Yue-Sheng; Dong, Zhi-Bing (Synthesis, 2018)
A convenient and efficient copper-catalyzed S-arylation of arylthioureas using diaryliodonium salts is reported. The desired arylisothioureas were synthesized in good yields in the presence of CuCl as catalyst and K2CO3 as base, and a wide variety of functional groups on the arylthioureas and diaryliodonium salts were tolerated. The protocol affords an alternative synthesis of some potentially useful biological and pharmaceutical compounds.
Keywords: copper; S-arylation; arylthioureas; diaryliodonium salts; synthesis